Difficulties experienced by pregnant teenagers and nursing care: Integrative review of the literature (Research, Society and Development, 2023)
Objective: to analyze the difficulties and coping strategies of pregnant adolescents and the role of nurses. Methodology: An Integrative Literature Review was carried out, searching the LILACS and SCIELO databases using the descriptors "pregnancy", "adolescence" and "nursing". Original articles published between 2019 and 2023 were included. Results: Pregnant teenagers face financial difficulties, the need to acquire new knowledge and adapt to a new routine, beyond feelings about pregnancy and the future, lack of social and family support and difficulties related to health services. In relation to nursing care, positive interaction and qualified listening between the team and pregnant women and a welcoming environment and encouraging autonomy are fundamental to promoting safety and well-being. Conclusion: Nursing professionals and the healthcare team must be prepared to meet the specific needs of pregnant adolescents, offering support, guidance and empathy through a humanized and individualized approach to teenagers.